Content analysis of area concept in higher education - Villamil-Rincón, Diana Lucía; Aldana-Bermúdez, Eliécer; Wagner-Osorio, Graciela (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article proposes a task to help first semester students of technology in topography at Quindío University to build the concept of area. The didactic design was based on the content analysis of area concept at university level, taking into account the following curriculum organizers: conceptual structure, representation systems and phenomenology. A diagnostic task was analyzed in which the students had to realize the design of the figure to locate a garden into a mall. The area of the task is not expressed by a numerical value or units of measurement. The aim is to establish a comparison between two squared areas by means of the ratio between them. The results show that a meaningful task was designed for students since it is a problem solving of the concept of area in the topographical context. The students must apply their previous knowledge to solve this challenging task because of the lack of measurements in the graphical representation which forces them to develop a more complex abstract level than to apply a simple algorithm.